Improved agricultural water management in the Nile Basin: development of a knowledge base - Rebelo, Lisa-Maria (IWMI/ILRI, 2009)
This poster illustrates the Participatory Impact Pathway Analysis conducted in consultation with stakeholders to identify the problems in the Nile basin and ensure impact.